The Bovine Practitioner 2016
DOI: 10.21423/bovine-vol50no2p154-164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delayed respiratory viral vaccine and/or inclusion of an immunostimulant on feedlot health, performance, and carcass merits of auction-market derived feeder heifers

Abstract: A total of 5,179 high-risk heifer calves were used to define the potential benefits of delaying the on-arrival respiratory viral vaccine (Pyramid® 5, Boehringer Ingelheim Vetmedica, Inc., St. Joseph, M0] for 30 d with and without the addition of a DNA immunostimulant (Zelnate® DNA Immunostimulant, Bayer Animal Health, Shawnee Mission, KS) at feedlot entry on health, performance, and carcass characteristics. The products were evaluated in a 2 x 2 factorial, randomized complete-block design comparing the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Each summary of the studies we evaluated includes a list of the current manufacturer, brand name, and the viruses included in the MLV respiratory vaccine administered. It is important to note that different vaccines and protocols were tested in the two studies we evaluated (Hagenmaier et al, 2018;and Rogers et al, 2016). Therefore, although both studies provide evidence for our question related to delayed vs on-arrival MLV use, they do not provide consistent evidence in terms of products used.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 90%
See 3 more Smart Citations
“…Each summary of the studies we evaluated includes a list of the current manufacturer, brand name, and the viruses included in the MLV respiratory vaccine administered. It is important to note that different vaccines and protocols were tested in the two studies we evaluated (Hagenmaier et al, 2018;and Rogers et al, 2016). Therefore, although both studies provide evidence for our question related to delayed vs on-arrival MLV use, they do not provide consistent evidence in terms of products used.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 90%
“…However, it also introduces variability into the results of this Knowledge Summary as much of the prior health data and origin data are unknown. Another limitation is that the two studies considered in this Knowledge Summary only explored delayed vaccination in heifers, therefore the impact of gender, if any, cannot be evaluated (Hagenmaier et al, 2018;and Rogers et al, 2016). Finally, the fact that both studies had less animals per pen than would typically be found in a commercial setting could influence the external validity of the results as respiratory disease dynamics are often different when the pen size is smaller.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%
See 2 more Smart Citations